Grant Support as a Research Development Factor in Russian Universities - Yulia N. Ebzeeva (Peoples' Friendship University of Russia (RUDN University), 2022)
Scientific research at the present stage of development of higher education is the basis of the academic reputation of the university, an aspect of the educational activities of the teacher and student. Quantitative indicators of scientific performance are the most important criterion for evaluating effectiveness at different levels. The article analyzes the implementation of scientific research based on grant support for four of the most authoritative foundations in Russia in 2006-2020: the Russian Foundation for Basic Research, the Russian Humanitarian Science Foundation, the Council for Grants of the President of the Russian Federation and the Russian Science Foundation. The assessment was made on the example of projects in the humanities and social sciences, including linguistics. The conclusion of the study introduces a statement of the importance of funds for the preservation of classical areas of scientific activity. It also demonstrates the necessity of an increase in the number of scientific research at Russian universities funded by these funds both in general terms and in relation to the number of grant projects conducted at academic institutions and an assessment of the activities of funds as a structure that determines priority directions of research. The most popular contests for universities have become contests in the areas of fundamental research and research support for young scientists.